2023
DOI: 10.1177/21582440231216568
|View full text |Cite
|
Sign up to set email alerts
|

How Does Commitment Affect Employee’s Innovative Behavior? A Time-Lagged Study

Peng Wang,
Yong Hou

Abstract: The employee’s innovative behavior plays an important role in the process of hotel operation. The purpose of this study was to examine the mechanisms by which hotel industry employees’ commitment affects innovative behavior, examining the mediating role of job involvement and the moderating role of superior-subordinate guanxi (SSG). The study collected 127 hotel supervisors’ questionnaires and 694 hotel employees’ questionnaires from Shandong Province. Results show that employees’ organizational and supervisor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Similarly, supervisor's justice, support and trust in the leader might lead to supervisory commitment (Akram, Kamran, Iqbal, Habibah, & Ishaq, 2018). Furthermore, supervisory commitment leads to several positive outcomes such as employee participation (Joo, Byun, Jang, & Lee, 2018), proactivity (Singh & Rangnekar, 2020), change readiness (Seggewiss, Straatmann, Hattrup, & Mueller, 2019), employee creativity (Imam et al, 2020), well-being and job satisfaction (Huyghebaert, Gillet, Becker, Kerhardy, & Fouquereau, 2017), job involvement and innovative behavior (Wang & Hou, 2023). Similarly, supervisory commitment decreases counterproductive work behavior and follower turnover (Smallfield et al, 2023).…”
Section: Supervisory Commitmentmentioning
confidence: 99%
“…Similarly, supervisor's justice, support and trust in the leader might lead to supervisory commitment (Akram, Kamran, Iqbal, Habibah, & Ishaq, 2018). Furthermore, supervisory commitment leads to several positive outcomes such as employee participation (Joo, Byun, Jang, & Lee, 2018), proactivity (Singh & Rangnekar, 2020), change readiness (Seggewiss, Straatmann, Hattrup, & Mueller, 2019), employee creativity (Imam et al, 2020), well-being and job satisfaction (Huyghebaert, Gillet, Becker, Kerhardy, & Fouquereau, 2017), job involvement and innovative behavior (Wang & Hou, 2023). Similarly, supervisory commitment decreases counterproductive work behavior and follower turnover (Smallfield et al, 2023).…”
Section: Supervisory Commitmentmentioning
confidence: 99%
“…They develop a positive work attitude and exhibit productive and effective behavior, which encourages the emergence of innovative ideas and innovative behaviors. Wang & Hou (2023) found that the higher an employee's emotional commitment to the organization, the more emotionally connected the employee is to the organization and the more likely they are to engage in innovative behaviors that benefit the organization. Becker (1960) believes that the employee's sense of belonging to the organization manifests itself primarily in the employee's dependence on the organization, i.e.…”
Section: Organizational Commitment and Innovative Behaviormentioning
confidence: 99%